An Exploratory Study of Spectroscopic Glutamatergic Correlates of Cortical Excitability in Depressed Adolescents - Lewis, Charles P.; Port, John D.; Frye, Mark A.; Vande Voort, Jennifer L.; Ameis, Stephanie H.; Husain, Mustafa M.; Daskalakis, Zafiris J.; Croarkin, Paul E. (Frontiers in Neural Circuits, 2016)
Introduction: Transcranial magnetic stimulation (TMS) research has suggested dysfunction in cortical glutamatergic systems in depression, while proton magnetic resonance spectroscopy (1H-MRS) studies have demonstrated deficits in concentrations of glutamatergic metabolites in depressed individuals in several cortical regions, including the anterior cingulate cortex (ACC). However, few studies have combined TMS and MRS methods to examine relationships between glutamatergic neurochemistry and excitatory and inhibitory neural functions, and none have utilized TMS-MRS methodology in clinical populations or in youth. This exploratory study aimed to examine relationships between TMS measures of cortical excitability and inhibition and concentrations of glutamatergic metabolites as measured by 1H-MRS in depressed adolescents. Methods: Twenty-four children and adolescents (aged 11-18 years) with depressive symptoms underwent TMS testing, which included measures of the resting motor threshold (RMT), cortical silent period (CSP), short-interval intracortical inhibition (SICI), and intracortical facilitation (ICF). Fourteen participants from the same sample also completed 1H-MRS in a 3 T MRI scanner after TMS testing. Glutamate + glutamine (Glx) concentrations were measured in medial ACC and left primary motor cortex voxels with a TE-optimized PRESS sequence. Metabolite concentrations were corrected for cerebrospinal fluid after tissue segmentation. Pearson product-moment and Spearman rank-order correlations were calculated to assess relationships between TMS measures and [Glx]. Results: In the left primary motor cortex voxel, [Glx] had a significant positive correlation with the RMT. In the medial ACC voxel, [Glx] had significant positive correlations with ICF at the 10-ms and 20-ms ISIs. Conclusions: These preliminary data implicate glutamate in cortical excitatory processes measured by TMS. Limitations included small sample size, lack of healthy control comparators, possible age- and sex-related effects, and observational nature of the study. Further research aimed at examining the relationship between glutamatergic metabolite concentrations measured through MRS and the excitatory and inhibitory physiology measured through TMS is warranted. Combined TMS-MRS methods show promise for future investigations of the pathophysiology of depression in adults as well as in children and adolescents.